Atropine does not prevent hypoxemia and bradycardia in tracheal intubation in the pediatric emergency department: observational study - Vitor Emanoel de Lemos Carvalho; Thomaz Bittencourt Couto; Bruno Marcelo Herculano Moura; Cláudio Schvartsman; Amélia Gorete Reis (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: The benefit of atropine in pediatric tracheal intubation is not well established. The objective of this study was to evaluate the effect of atropine on the incidence of hypoxemia and bradycardia during tracheal intubations in the pediatric emergency department. Methods: This is a single-center observational study in a tertiary pediatric emergency department. Data were collected on all tracheal intubations in patients from 31 days to incomplete 20 years old, performed between January 2016 and September 2020. Procedures were divided into two groups according to the use or not of atropine as a premedication during intubation. Records with missing data, patients with cardiorespiratory arrest, cyanotic congenital heart diseases, and those with chronic lung diseases with baseline hypoxemia were excluded. The primary outcome was hypoxemia (peripheral oxygen saturation ≤88%), while the secondary outcomes were bradycardia (decrease in heart rate >20% between the maximum and minimum values) and critical bradycardia (heart rate <60 bpm) during intubation procedure. Results: A total of 151 tracheal intubations were identified during the study period, of which 126 were eligible. Of those, 77% had complex, chronic underlying diseases. Atropine was administered to 43 (34.1%) patients and was associated with greater odds of hypoxemia in univariable analysis (OR: 2.62; 95%CI 1.15-6.16; p=0.027) but not in multivariable analysis (OR: 2.07; 95%CI 0.42-10.32; p=0.37). Critical bradycardia occurred in only three patients, being two in the atropine group (p=0.26). Bradycardia was analyzed in only 42 procedures. Atropine use was associated with higher odds of bradycardia in multivariable analysis (OR: 11.00; 95%CI 1.3-92.8; p=0.028). Conclusions: Atropine as a premedication in tracheal intubation did not prevent the occurrence of hypoxemia or bradycardia during intubation procedures in pediatric emergency.